Digital Transformation and Bank Performance: The Moderating Role of Risk in Indonesian Commercial Banks - Febriansyah, Wivan; Ermawati, Wita Juwita; Fariyanti, Anna; Syukur, Mat (Universitas Muhammadiyah Surakarta, 2025)
This study analyzes the effect of digital transformation on the performance of Indonesian commercial banks, with financial risk measured by the Z-Score as a moderating variable. Using panel data regression on 21 listed banks from 2019 to 2023, the findings reveal that digital transformation has a positive and significant impact on Net Interest Margin (NIM), reflecting improved efficiency and profitability. However, when financial risk is considered, the direct effect of digital transformation becomes insignificant, suggesting that risk conditions may hinder the optimal benefits of digital initiatives. Interestingly, the interaction term between digital transformation and Z-Score is positive and significant, indicating that banks with higher financial stability are better positioned to leverage digital technologies. Furthermore, leverage and Non-Performing Loans (NPLs) show significant effects, while macroeconomic factors such as inflation and GDP growth are insignificant. These results highlight that the success of digital transformation depends not only on technology adoption but also on financial soundness and effective risk management. The findings provide practical implications for regulators and banking practitioners in designing sustainable digital transformation strategies that enhance competitiveness in the digital era.